Effects of branched-chain amino acids on Shiraia perylenequinone production in mycelium cultures - Wen Hao Shen; Rui Peng Cong; Xin Ping Li; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (Microbial Cell Factories, 2023)
Abstract Background Perylenequinones from Shiraia fruiting bodies are excellent photosensitizers and widely used for anti-cancer photodynamic therapy (PDT). The lower yield of Shiraia perylenequinones becomes a significant bottleneck for their medical application. Branched-chain amino acids (BCAAs) not only serve as important precursors for protein synthesis, but also are involved in signaling pathway in cell growth and development. However, there are few reports concerning their regulation of fungal secondary metabolism. In present study, the eliciting effects of BCAAs including l-isoleucine (l-Ile), l-leucine (l-Leu) and l-valine (l-Val) on Shiraia perylenequinone production were investigated. Results Based on the analysis of the transcriptome and amino acid contents of Shiraia in the production medium, we revealed the involvement of BCAAs in perylenequinone biosynthesis. The fungal conidiation was promoted by l-Val treatment at 1.5 g/L, but inhibited by l-Leu. The spore germination was promoted by both. The production of fungal perylenequinones including hypocrellins A (HA), HC and elsinochromes A-C (EA–EC) was stimulated significantly by l-Val at 1.5 g/L, but sharply suppressed by l-Leu. After l-Val treatment (1.5 g/L) in Shiraia mycelium cultures, HA, one of the main bioactive perylenequinones reached highest production 237.92 mg/L, about 2.12-fold than that of the control. Simultaneously, we found that the expression levels of key genes involved in the central carbon metabolism and in the late steps for perylenequinone biosynthesis were up-regulated significantly by l-Val, but most of them were down-regulated by l-Leu. Conclusions Our transcriptome analysis demonstrated that BCAA metabolism was involved in Shiraia perylenequinone biosynthesis. Exogenous BCAAs exhibit contrasting effects on Shiraia growth and perylenequinones production. l-Val could promote perylenequinone biosynthesis via not only enhancing the central carbon metabolism for more precursors, but also eliciting perylenequinone biosynthetic gene expressions. This is the first report on the regulation of BCAAs on fungal perylenequinone production. These findings provided a basis for understanding physiological roles of BCAAs and a new avenue for increasing perylenequinone production in Shiraia mycelium cultures. Graphical Abstract